2012
DOI: 10.1085/jgp.201210883
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4–dependent K+ and water transport modeled in brain extracellular space following neuroexcitation

Abstract: Potassium (K+) ions released into brain extracellular space (ECS) during neuroexcitation are efficiently taken up by astrocytes. Deletion of astrocyte water channel aquaporin-4 (AQP4) in mice alters neuroexcitation by reducing ECS [K+] accumulation and slowing K+ reuptake. These effects could involve AQP4-dependent: (a) K+ permeability, (b) resting ECS volume, (c) ECS contraction during K+ reuptake, and (d) diffusion-limited water/K+ transport coupling. To investigate the role of these mechanisms, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 61 publications
1
72
0
Order By: Relevance
“…AQP4 deficiency is associated with a slower rate of potassium reuptake by astrocytes following neuroexcitation 59,61 , which — as supported by mathematical modelling — may be related to a reduced electrochemical driving force for potassium reuptake caused by slowed astrocyte water uptake and contraction of the extracellular space 62 . AQP4-deficient mice also have impaired glial scar formation, which may be related to defective astrocyte migration 63,64 .…”
Section: Biological Function Of Aqps In Mammalsmentioning
confidence: 80%
“…AQP4 deficiency is associated with a slower rate of potassium reuptake by astrocytes following neuroexcitation 59,61 , which — as supported by mathematical modelling — may be related to a reduced electrochemical driving force for potassium reuptake caused by slowed astrocyte water uptake and contraction of the extracellular space 62 . AQP4-deficient mice also have impaired glial scar formation, which may be related to defective astrocyte migration 63,64 .…”
Section: Biological Function Of Aqps In Mammalsmentioning
confidence: 80%
“…In the healthy CNS, astrocytes (1) maintain the extracellular homeostasis of K þ , water, pH, and transmitter uptake (Halassa and Haydon 2010;Jin et al 2013), (2) may modulate synaptic activity directly via release of "gliotransmitters" (Volterra and Meldolesi 2005;Halassa and Haydon 2010;Hamilton and Attwell 2010;Henneberger et al 2010), and (3) take part in the formation and pruning of synapses (Chung et al 2013;Clarke and Barres 2013). Functional changes undergone by reactive astrocytes in response to specific molecular triggers can impact neurons via (1) down-regulation of glutamine synthase associated with reduced inhibitory synaptic currents in local neurons (Ortinski et al 2010), (2) increased expression of xCT (Slc7a11), a cysteine-glutamate transporter associated with increased glutamate signaling, seizures, and excitotoxicity (Jackman et al 2010;Buckingham et al 2011), and (3) changes in the expression of multiple GPCRs and G proteins and calcium signaling evoked by their ligands (Hamby et al 2012).…”
Section: Astrogliosis and Neuronal Function And Behaviormentioning
confidence: 99%
“…This could contribute to the delayed K ϩ clearance observed in animals lacking ␣-syntrophin. A recent modeling study concluded that AQP4 can regulate K ϩ uptake through effects on extracellular volume (73).…”
Section: Aqp4 In Brainmentioning
confidence: 99%